Chinese Immigration Law and Policy: A Case of ‘Change Your Direction, or End Up Where You Are Heading’? - Zhu, Guobin; Price, Rohan (Columbia Journal of Asian Law, 2013)
Laozi’s famous call for reform in the title of this paper is a useful metaphor for the need to address the outdated settings that constitute much of China’s policy toward resident aliens. This is because unless there is improvement in the laws, there will be more social and economic exclusions of migrant populations at a time when cohesion is politically paramount. Formalizing the position of resident aliens presents a unique economic opportunity for China to harness such people with an assimilation policy. In turn, this will increase the nation’s revenue base and enlarge the polity’s conception of what it is to be a Chinese. By translating from Chinese to English the views of a range of academics, policy makers, and local officials, this article makes available to a Western audience the Middle Kingdom’s increasingly contentious discourse on immigration. By reviewing the 1985 Law of the People’s Republic of China on the Control of Entry and Exit ofAliens and the 2012 Law of the People’s Republic of China on the Administration of Exit and Entry, this article argues that the Chinese immigration law is at a crossroad. By making a special reference to African nationals immigrating to Guangzhou City, this article surveys the law to establish what is wrong with it and how it needs to be changed.